Millennium Units, Intercultural Bilingual Education and (in) equality in access to education in Ecuador. An analysis from ethnographic research - Marta Rodriguez Cruz (Runa, 2017)
This paper is part of a doctoral research project that analyzes whether the public management of intercultural bilingual education responds to the definition of Ecuador as an intercultural and plurinational state. The article analyzes the educational policy developed through Millennium units, promoted by the Ministry of Education and directed especially to indigenous population, in a situation of social vulnerability due to poverty. Our analysis follows a double itinerary: first, the paper analyzes the current legislation on bilingual intercultural education, the Millennium units and the universalization of access to education; secondly, bilingual intercultural education practices and the generalization of access to the educational system are studied and described, based on an ethnography developed in two Millennium units located in the Ecuadorian Andes.